Computation of Sombor Indices for Some Classes of Silicon Carbides - Mohamad Nazri Husin, Ghulam Mohyuddin, Faraha Ashraf, Murat Cancan, Mehdi Alaeiyan, Mohammad Reza Farahani, Muhammad Shoaib Sardar (Mathematical Statistician and Engineering Applications, 2022)
An index from which we can predict different properties of the molecule of a molecular graph without doing any experiment is called topological index. Silicon carbide is a semiconductor crystalline compound formed by silicon and carbon. The crystal of Silicon carbide is like a closely attached structure in which atoms have covalent bonds between them. In this paper, the molecular graphs of silicon carbide are discussed and further we calculated the exact formulas of Sombor index for these Silicon carbides. The offered results can help to analyse several chemical or physical properties of the Silicon carbides. These methods will be helpful to save time and money in developing new resources, compounds and medications, which is very useful for the betterment of mankind.